Physic and physis: Didactic specific interactions - Müller, Andreas (Swiss Journal of Educational Research, 2018)
A double tension between physics and (biological, corporal) physis is derived on a conceptual and epistemological level, leading to genuine didactical questions. On the one hand, a cognitive tension, genereted by the «disembodiment», the strong abstraction within physics. On the other hand, the loss of direct sensations, yielded by the abandonment of corporeality physis, and which leads to large motivation problems. Referring to various lines of research in science education and educational science, these questions are discussed following two guiding ideas: «The body as context in physics education: Connecting to the lifeworld and the self of learners» for the motivational aspects, and «The body as medium of physics education: schème moteur, operational intelligence, kinesthetic feedback» for the cognitive aspects. On this basis, perspectives for research and education are addressed.